Return of investment initiatives in business process management - Pereira, L.; Sabido, P.; Santos, J. (2019 IEEE International Conference on Engineering, Technology and Innovation (ICE/ITMC), 2019)
This study aims to verify the perception of Business Process Management (BPM), namely benefits, maturity, budget in the company and qualitative factors that make it difficult to measure and to understand the relevance of Return of Investment (ROI). It's also intended to create a conceptual model that makes it possible to evaluate the Valorisation of BPM within an organization. The results indicate that BPM has gained higher relevance and maturity in organizations, being noticed through the high range of Budget that is allocated to BPM initiatives, as well as the higher outsourcing services and internal teams. Regarding the barriers of ROI's implementation, the one which is the most common one was the Top Managers. This study had limitations at the sample level and for future research these limitations should be overcome with the study of the dependency between Economic Value Added and Earnings Per Share and BPM Budget variables using ROI.